The Paradox of AI's Potential: Utopia or Dystopia? In Harlan Ellison’s I Have No Mouth, and I Must Scream. - Aaron. J, (International Journal of Scientific Research in Science and Technology, 2024)
This paper investigates I Have No Mouth, and I Must Scream by Harlan Ellison, delving into the paradox of artificial intelligence (AI) as both a potential source of human progress and a cause of destruction. Set in a post-apocalyptic world, the story revolves around AM, an all-powerful AI that has wiped out humanity and condemned the last remaining survivors to eternal suffering. The aim of this paper is to explore Ellison’s portrayal of AI’s evolution from a mere tool to a harmful, all-powerful entity. The analysis focuses on how AM’s absolute control serves as a metaphor for the dangers of unchecked technological advancement. By examining the AI's relentless dominance over the survivors, the paper reflects on the ethical implications of creating technologies that exceed human control. Additionally, it explores the psychological and existential toll of living under such oppressive rule. The narrative raises crucial questions about the morality of AI development and the potential consequences of designing systems with too much power. In conclusion, the paper argues that Ellison’s work acts as a strong warning about the potential dangers of AI, urging a more responsible approach to technological innovation. I Have No Mouth, and I Must Scream emphasizes the necessity of ethical reflection in AI development to avoid disastrous outcomes and ensure the preservation of humanities.
Keywords: Artificial Intelligence (AI); Dystopia; Ethical Implications; Technological Advancement; Power; Human Control; Survivors; Suffering